The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1371/journal.pone.0117830
|View full text |Cite
|
Sign up to set email alerts
|

The Expression and Regulation of Chemerin in the Epidermis

Abstract: Chemerin is a protein ligand for the G protein-coupled receptor CMKLR1 and also binds to two atypical heptahelical receptors, CCRL2 and GPR1. Chemerin is a leukocyte attractant, adipokine, and antimicrobial protein. Although chemerin was initially identified as a highly expressed gene in healthy skin keratinocytes that was downregulated during psoriasis, the regulation of chemerin and its receptors in the skin by specific cytokines and microbial factors remains unexplored. Here we show that chemerin, CMKLR1, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(96 citation statements)
references
References 53 publications
3
87
0
5
Order By: Relevance
“…Consistent with this notion, we detected significantly high Chemerin concentrations in senescent dermal fibroblasts in vitro, as well as in the dermal fibroblasts of old healthy individuals and in the stromal fibroblasts of old cSCC patients in situ . This expression pattern was significantly different in the young healthy skin, exhibiting lower Chemerin abundance in the dermis vs. epidermis, as previously demonstrated by Banas et al [56]. Interestingly, in line with a previous publication [57] we found that Chemerin production was significantly decreased in cSCC cells compared to normal keratinocytes.…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with this notion, we detected significantly high Chemerin concentrations in senescent dermal fibroblasts in vitro, as well as in the dermal fibroblasts of old healthy individuals and in the stromal fibroblasts of old cSCC patients in situ . This expression pattern was significantly different in the young healthy skin, exhibiting lower Chemerin abundance in the dermis vs. epidermis, as previously demonstrated by Banas et al [56]. Interestingly, in line with a previous publication [57] we found that Chemerin production was significantly decreased in cSCC cells compared to normal keratinocytes.…”
Section: Discussionsupporting
confidence: 89%
“…Future studies using knockdown approaches could address this point. It is unlikely that GPR1 and APJ serve as coreceptors for SIVagmSab in PBMC, given the low-level function the we found in transfected cells and limited evidence (in humans and rodents at least) for expression on CD4 ϩ T cells (66)(67)(68)(69)(70). Finally, while we tested all of the major alternative coreceptors that have been reported for various SIVs, it is possible that there are other, as-yet-unidentified seven-transmembrane receptor (7TMR) molecules that could also mediate entry.…”
Section: Discussionmentioning
confidence: 85%
“…qPCR was performed using GoTaq ® qPCR Master Mix (Promega) and primers specific for P. gingivalis proteases (32): rgpA , 5′-TATCCTTCGTGATGTGCGTG-3′, 5′-GCTGTAACGGGAGAAGCAAT-3′; rgpB , 5′-CATTCTCCTCTCTGTTGGGA-3′, 5′-CGTAGGGGATTTGATCAGGA-3′; kgp , 5′-TCAAGCAGT CGATGCAAGC-3′, 5′-ACTTGGGTCAGTTCTTGTCC-3′; and sod , 5′-AATTCCACCACGGTAAGCAC-3′, 5′-TTCTCGATGGACAGTTTGCC-3′; as well as human chemerin 5′-TGGAAGAAACCCGAGTGCAAA-3′, 5′-AGAACTTGGGTCTCTATGGGG-3′, and GAPDH, 5′-GACAGTCAGCCGCATCTTCT-3′, 5′-TTAAAAGCAGCCCTGGTGAC-3′. The relative gene expression normalized to sod (rgpA, rgpB, kgp) and GAPDH (chemerin) was calculated using the 2 −ΔΔCT method (10, 33, 34). …”
Section: Methodsmentioning
confidence: 99%
“…However, proteases can also inactivate or degrade the attractant and thus limit the extent of chemerin activity (1). Chemerin is broadly expressed in numerous anatomic sites, including liver and fat tissues as well as by epithelial cells in the skin epidermis (710), intestinal epithelium (8, 11), and pulmonary airways (8, 12). The strategic positioning of chemerin at the host-environment interface suggests a role in antimicrobial defense.…”
Section: Introductionmentioning
confidence: 99%